1997
DOI: 10.1046/j.1365-2141.1997.9662656.x
|View full text |Cite
|
Sign up to set email alerts
|

Which compartments are involved in Philadelphia‐chromosome positive chronic myeloid leukaemia? An answer at the single cell level by combining May‐Grünwald‐Giemsa staining and fluorescence in situ hybridization techniques

Abstract: Summary. Chronic myeloid leukaemia (CML) is believed to represent a stem cell disorder involving all three cell lineages. The typical chromosomal aberration, the Philadelphia chromosome, is the translocation (9;22)(q34;q11). Several studies with cytogenetics, fluorescence in situ hybridization (FISH), or polymerase chain reaction have investigated the presence of the t(9;22) in different cell compartments. However, questions still remain. In six cases of CML we combined the standard May-Grü nwald-Giemsa staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 37 publications
3
41
1
1
Order By: Relevance
“…In CML, the LSC appear to be very similar if not identical to normal HSC, with multilineage differentiation capacity in patients (Haferlach et al, 1997) and multilineage repopulating activity in NOD-SCID mice Eisterer et al, 2005). In mouse models, whereas transgenic expression of BCR-ABL in CMP causes a CML-like phenotype (Jaiswal et al, 2003), retroviral expression of BCR-ABL in purified CMP or GMP does not produce MPD in recipient mice (Huntly et al, 2004).…”
Section: Leukemia Stem Cell Signaling Pathwaysmentioning
confidence: 99%
“…In CML, the LSC appear to be very similar if not identical to normal HSC, with multilineage differentiation capacity in patients (Haferlach et al, 1997) and multilineage repopulating activity in NOD-SCID mice Eisterer et al, 2005). In mouse models, whereas transgenic expression of BCR-ABL in CMP causes a CML-like phenotype (Jaiswal et al, 2003), retroviral expression of BCR-ABL in purified CMP or GMP does not produce MPD in recipient mice (Huntly et al, 2004).…”
Section: Leukemia Stem Cell Signaling Pathwaysmentioning
confidence: 99%
“…Similar findings were recently reported by Muhlman et al, 23 who calculated the proportion of BCR/ABL + nuclei relative to the percentage of myeloid elements, in order to reduce counting errors deriving from the presence of B or T lymphocytes. The involvement of lymphocytes in CML is a matter of controversy and this issue was recently studied and reviewed by Haferlach and colleagues, 24 who showed that 25-50% of lymphocytes carried BCR/ABL fusion in CML chronic phase.…”
Section: Figurementioning
confidence: 99%
“…2,[42][43][44][45] There is some controversy over whether lymphocytes are of leukemia origin in CML. Garicochea et al 46 reported that T lymphocytes had no bcr/abl fusion gene, while Tefferi et al 42 demonstrated that t(9;22) was detectable in 34% of CD3-positive T lymphocytes, in 32% of CD19-positive B lymphocytes and in 82% of CD34-positive precursor cells.…”
Section: Discussionmentioning
confidence: 99%